233k views
3 votes
Uh anyone? and please explain


Uh anyone? and please explain ​-example-1

1 Answer

5 votes

a) The solution is x = -9.

b) The solution is x = 15.

Explanation:

a) The given equation is 3(x+1)=2(x-3).

To solve this equation, distributive property is used.

The Distributive property :

It is done by multiplying the number outside the bracket with each terms present inside the bracket.

Now, the first step is to multiply 3 with each terms in (x+1) and multiply 2 with each terms in (x-3).

⇒ 3x+3 = 2x-6

Bring x terms on one side and constants on other side,

⇒ 3x-2x = -6-3

⇒ x = -9

b) The given equation is 2(5x-6)=3(3x+1).

To solve this equation,distributive property is used.

Now the first step is to multiply 2 with each terms of (5x-6) and 3 with each terms of (3x+1).

⇒ 10x-12 = 9x+3

Bring x terms on one side and constants on other side,

⇒ 10x-9x = 3+12

⇒ x = 15

User Unorsk
by
7.8k points